2019
DOI: 10.3390/nu11081824
|View full text |Cite
|
Sign up to set email alerts
|

Diet in Irritable Bowel Syndrome (IBS): Interaction with Gut Microbiota and Gut Hormones

Abstract: Diet plays an important role not only in the pathophysiology of irritable bowel syndrome (IBS), but also as a tool that improves symptoms and quality of life. The effects of diet seem to be a result of an interaction with the gut bacteria and the gut endocrine cells. The density of gut endocrine cells is low in IBS patients, and it is believed that this abnormality is the direct cause of the symptoms seen in IBS patients. The low density of gut endocrine cells is probably caused by a low number of stem cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
153
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(162 citation statements)
references
References 157 publications
1
153
1
7
Order By: Relevance
“…Regular meals, taking time to eat and avoiding missing meals or leaving long gaps between eating are not only basics rules of healthy diet, but also play the significant role in IBS management. [6] Furthermore, mentioned rules are beneficial in all subtypes of IBS. Apparently there is a higher prevalence of food trigger reactions in patients with IBS-D.…”
Section: Description Of the State Of Knowledge 31 The Importance Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Regular meals, taking time to eat and avoiding missing meals or leaving long gaps between eating are not only basics rules of healthy diet, but also play the significant role in IBS management. [6] Furthermore, mentioned rules are beneficial in all subtypes of IBS. Apparently there is a higher prevalence of food trigger reactions in patients with IBS-D.…”
Section: Description Of the State Of Knowledge 31 The Importance Ofmentioning
confidence: 99%
“…The most common examples are: coffee, fried and sweetened products, alcohol and sweets. [6] The aim of this study was to describe dietary modifications that alleviate symptoms and improve quality of life. Study material consisted of publications, which were found in PubMed, ResearchGate and Google Scholar databases.…”
Section: Introduction and Purposementioning
confidence: 99%
“…This low enteroendocrine-cell density appears to be caused by both the low density of intestinal stem cells and the low rate of stem cells differentiation into enteroendocrine cells [15]. In one of the articles in this issue, it is speculated that by-products resulting from bacterial fermentation of the diet interact with gut stem cells causing the low differentiation rate into endocrine cells, leading to the manifestation of gastrointestinal dysmotility, visceral hypersensitivity, and abnormal gastrointestinal secretion [1]. This in turn would give rise to the symptoms characteristic of IBS.…”
Section: Role Of Diet In the Pathophysiology Of Ibsmentioning
confidence: 99%
“…The intestinal bacterial profile in patients with IBS differs from that in healthy subjects, with IBS patients having a lower bacterial diversity (dysbiosis). Patients with IBS who do not respond to dietary management suffer from severe dysbiosis [1]. The article in this issue by Catinean et al [18] indicates that a mixture of spores from five Bacillus spp.…”
Section: Role Of Probiotics Supplements In Managing Ibsmentioning
confidence: 99%
See 1 more Smart Citation